PENYULUHAN HUKUM EKONOMI SYARIAH TERHADAP WARGA DESA CIBIRU WETAN KECAMATAN CILEUNYI KABUPATEN BANDUNG - iwan setiawan; Ramdani Wahyu Sururie (Pusat Pengabdian kepada Masyarakat LP2M UIN Sunan Gunung Djati Bandung, 2019)
Sharia economics has two legal basis of sharia economic systems, namely the Qur'an and the Sunnah of the Prophet, the laws taken from the two basic foundations in concept and principle are fixed (cannot change anytime and anywhere). The Purpose of sharia economic law counseling towards residents of Cibiru Wetan Village, Cileunyi District, Bandung Regency are: a) Providing knowledge and insight to extension participants, the residents of Cibiru Wetan Village, Cileunyi District, Bandung Regency related to sharia economic law material and b) Providing knowledge and insight and the skills of the counseling participants about the advantages of sharia economic law.To solve the problems that have been identified and formulated above, the counseling can run as an alternative problem solving is as follows: counseling is done with individual and classical approaches. The classical approach is carried out when giving a theory about sharia economic law and an individual approach is carried out during training. The results of community service, sharia economic law counseling in the community of Cibiru Wetan Village, Cileunyi District, Bandung Regency; 1) The extension of Islamic economic law in the community of Cibiru Wetan Village, Cileunyi District, Bandung Regency has benefited the community. This is evident from the enthusiasm of the community in question and answer and motivated to develop their business creativity. So that this activity needs to be carried out continuously and 2) The forms of activities carried out are intensive counseling with the following stages: Lecture on introducing the importance of sharia economic law; Lecture on sharia economic law theories; Lecture on the development of sharia economic law; Demonstration of the steps to develop and develop sharia economic law; Simulation training on the application of sharia economic law; and evaluation of results